The Development of an Educational Writing Game Application for Preschool Children Based on User Centered Design (UCD) Methodology - Wan Nurul Amira, Wan Mohd Razani (2010)
An educational game is one of the poweful tools for helping people especially preschool children in their learning but there are some problems with this application. There are many game applications but the content and navigation does not meet criteria for preschool children to learn. Besides, the application is much limited and the content towards to entertainment. Navigation of user interface also one of the problem in the application because it so hard and difficult for children to use it. The main objective of this project is to identify the content requirement that is needed and develop an educational writing game for preschool children for the ages four until six years old. In this project, user-centered design (UCD) will be used as a methodology to achieve an objective. Hence, this application can be tested by preschool children in Sekolah Rendah Kebangsaan Bukit Pinang and Sekolah Kebangsaan Sultanah Asma and the positive responds that been received and achieve the objective of the project. From this, the accuracy of children handwriting will be determined. The writing games specifically on mathematic area such as preschool children write the number.